Is Spinal Cord Stimulation Useful and Safe for the Treatment of Chronic Pain of Ischemic Origin? A Review. Issue 1 (January 2016) - Kinfe, Thomas M.; Pintea, Bogdan; Vatter, Hartmut
Abstract : Objectives: The scope of this literature review was to assess the safety and the efficacy of spinal cord stimulation (SCS) for the treatment of chronic pain syndromes originating from refractory angina pectoris and peripheral vascular disease compared with conservative management. Materials and Methods: A literature review was performed, which included randomized controlled trials and prospective controlled trials. PubMed searches were performed using terms such as SCS, RCT, vascular, VAS, heart, legs, limbs, and angina pectoris. Conservative management consisted of antihypertensive, vasodilator, or anticoagulant medications, analgesics, and local wound care. Seven trials met the inclusion and exclusion criteria. Each trial was analyzed during different follow-up periods to determine whether the mean reduction in the visual analog scale score associated with SCS treatment reached the minimal clinically important difference and/or the minimal significant difference associated with adequate pain management. The number and the rate of complications during different follow-up periods were also evaluated for each trial. Results: The review demonstrated that SCS treatment provides in part long-term pain relief in otherwise intractable chronic pain of ischemic origin with a relatively low complication rate. Discussion: SCS is a minimally invasive and reversible pain intervention. On the basis of the current literature, SCS may be an alternative treatment strategy in refractory angina pectoris and peripheral vascular disease patients, presenting a low surgical risk profile. However, further clinical trials with larger sample sizes and extended follow-up are required to confirm this finding.